Business mathematics : for senior high school - Zorilla, Roland S.; Partible, Fe G.; Mendoza, Violeta C.; Bagano, Dominic C.; Bansa, Hazam E.; Esller, Beda H. (Malabon City : Mutya Publishing House, Inc., 2017)
This book on business mathematics for senior high school is designed particularly for grade 11 students under the K to 12 basic educations curriculum.
Chapter 1: Fundamentals operations on fractions, decimals and percentage.--Chapter 2: Ratio and proportion.--Chapter 3: Buying and selling products.--Chapter 4: Interests and commissions.--Chapter 5: Salaries and wages.--Chapter 6: Presentation analysis of business data.
Includes bibliography.
Keywords: BUSINESS MATHEMATICS